FDI Investment Incentive System and FDI Inflows: The Philippine Experience - Rafaelita M. Aldaba (Philippine Institute for Development Studies (PIDS), 2006)
This paper examines the countrys investment incentive program for foreign investors and its success in attracting substantial FDI inflows. The analysis compares the FDI incentive system and FDI performance of the Philippines with other Asian countries. Since it is difficult to untangle the effect of tax incentives from other factors, the analysis also takes into account other factors such as level of competitiveness, costs of doing business and availability of infrastructure. Our experience tends to suggest that in the absence of fundamental factors such as economic conditions and political climate, tax incentives alone are not enough to generate a substantial effect on investment decisions of investors nor can they compensate for the deficiencies in the investment environment.
Keywords: 330; investment incentives; corporate taxation; Foreign direct investment (FDI)